SILVER NANOPARTICLES IN DENTISTRY: A SCOPING REVIEW OF ANTIMICROBIAL ACTIVITY AND CLINICAL APPLICATIONS - Freitas, Kayky Adaan Holanda de; Costa, Izabelly Martins da; Magalhães, Thais Alves de; Rufino, João Paulo Ferreira; Furtado, Silvania da Conceição; Magalhães, Alessandra Alves da Silva (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2025)
Silver nanoparticles (AgNPs) have gained significant attention in dentistry due to their potent antimicrobial properties. This scoping review aimed to assess the antimicrobial activity of AgNPs and their applications across different dental specialties. The study followed the Joanna Briggs Institute (JBI) methodology. A total of 43 studies met the inclusion criteria and were categorized based on their focus areas. The findings indicate that AgNPs exhibit strong antimicrobial activity against oral pathogens such as Streptococcus mutans and Enterococcus faecalis, with applications ranging from orthodontic adhesives and root canal disinfectants to coatings for dental implants and prostheses. The review highlights that AgNPs can prevent microbial colonization, reduce biofilm formation, and serve as an alternative to traditional antimicrobial agents, potentially mitigating antibiotic resistance. However, concerns regarding their cytotoxicity and long-term biocompatibility persist. Further in vivo research is needed to validate their efficacy and safety in clinical settings. Future studies should focus on optimizing AgNP concentrations and assessing potential side effects. This review provides an overview of the current evidence on AgNPs in dentistry and emphasizes the importance of further research for their safe and effective clinical application.